Genom Editing of Saccharomyces Cerevisiae Using CRISPR-Cas9 System: A Review Study - Yaseen Ismael Imran; Ibrahim Abdulla Ahmed; Ahmed Ali Mhawesh (Journal La Lifesci, 2021)
Saccharomyces cerevisiae is an important yeast has been exploited for a long time to produce alcohol or bread. Moreover, genetically engineered S. cerevisiae cells continue to be used as cell factories for production of biofuels, pharmaceutical proteins and food additives. Genetically modified strain of S. cerevisiae created using traditional methods is laborious and time consuming. Recently, originally an immune system in archaea and bacteria, Clustered regularly interspaced short palindromic repeats “CRISPR” and CRISPR-associated “Cas” have been used exploited as a flexible tool for genome editing. Until now, this tool has been applied to many organisms including yeast. Here, we review the importance of S. cerevisiae as an industrial platform and the use of CRISPR/Cas system and its applications in research and industry of this yeast.